Perceptions of Boarding Careers, Students Majoring in Accounting and Non-Accounting Students on the Ethics of Preparing Financial Statements Based on Boarding School Psak (Case Study on Islamic Boarding Schools in Pekalongan) - Imam Prayogo; Annisa Qurrota Ayun; Muhammad Ubaidillah (Budapest International Research and Critics University, 2022)
Education in Indonesia lags far behind other countries in Asia. One of the causes is the lack of ethical implementation in the education system. Islamic boarding school education is generally organized by the community as a manifestation of education from, by, and for the community. Islamic boarding school is an Islamic educational institution with a dormitory or cottage system.One form of ethical violation that is still widely questioned in the accounting world is the issue of earnings management. Islamic boarding school caregivers and other administrators can be positioned as agents in Law No. 18 of 2019. This is because they get endowment funds from the central government and/or local governments. The principal here is the central government and/or local government because it provides endowment funds to Islamic boarding schools. Through PSAK Accounting for Islamic Boarding Schools, Islamic boarding schools are asked to present accountability in the form of financial reports. This study analyzes the differences in perceptions between boarding school caregivers, students majoring in accounting, students majoring in non-accounting, on the ethics of preparing financial statements. The results showed that there were no significant differences in perceptions in the three research samples, namely: boarding school caregivers, students majoring in accounting, and non-accounting students on the ethics of preparing financial statements.